Baltic herring hydrolysates: Identification of peptides, in silico DPP-4 prediction, and their effects on an in vivo mice model of obesity - Wang, Dongxu; Huang, Xin; Marnila, Pertti; Hiidenhovi, Jaakko; Välimaa, Anna-Liisa; Granato, Daniel; Mäkinen, Sari (Elsevier BV, 2024)
Baltic herring is the main catch in the Baltic Sea; however, its usage could be improved due to the low processing rate. Previously we have shown that whole Baltic herring hydrolysates (BHH) and herring byproducts hydrolysates (BHBH) by commercial enzymes consisted of bioactive peptides and had moderate bioactivity in in vitro dipeptidyl peptidase (DPP)-4 assay. In this study, we identified the hydrolysate peptides by LC-MS/MS and predicted the potential bioactive DPP-4 inhibitory peptides using in silico tools. Based on abundance, peptide length and stability, 86 peptides from BHBH and 80 peptides from BHH were proposed to be novel DPP-4 inhibitory peptides. BHH was fed to a mice intervention of a high-fat, high-fructose diet to validate the bioactivity. The results of the glucose tolerance and insulin tolerance improved. Plasma DPP-4 activities, C-peptide levels, and HOMA-IR scores significantly decreased, while plasma glucagon-like peptide-1 content increased. In conclusion, BHH is an inexpensive and sustainable source of functional antidiabetic ingredients.
Keywords: bioactive peptides; mass spectrometry; glucose homeostasis